2004
DOI: 10.1136/gut.2003.027789
|View full text |Cite|
|
Sign up to set email alerts
|

Is the mucosal route of administration essential for probiotic function? Subcutaneous administration is associated with attenuation of murine colitis and arthritis

Abstract: Background: We and others have reported the prophylactic efficacy of oral consumption of probiotic lactobacilli in the interleukin 10 knockout (IL-10 KO) model of colitis. It has not been demonstrated that the oral route is essential for probiotic efficacy. Aims: (i) To determine the effect of parenteral administration (subcutaneous) of Lactobacillus salivarius 118 on colitis of IL-10 KO mice; and (ii) to determine if observed responses are disease specific. Methods: (i) IL-10 KO mice were injected subcutaneou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(98 citation statements)
references
References 36 publications
2
94
0
2
Order By: Relevance
“…It has been shown that probiotics are capable of inhibiting the nuclear factor-kB pathway in epithelial cells through various mechanisms, including blocking inhibitor kB degradation by inhibiting ubiquination (Neish et al 2000) or by inhibiting proteasome function (Jijon et al 2004). Induction of Treg cells by certain probiotic bacterial strains has also been hypothesized to exert potent antiinflammatory effects (Sheil et al 2004). In contrast, during E. coli infection experiment, all measured inflammatory proteins recorded a remarkable increase in LR-fed group as compared to control group.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that probiotics are capable of inhibiting the nuclear factor-kB pathway in epithelial cells through various mechanisms, including blocking inhibitor kB degradation by inhibiting ubiquination (Neish et al 2000) or by inhibiting proteasome function (Jijon et al 2004). Induction of Treg cells by certain probiotic bacterial strains has also been hypothesized to exert potent antiinflammatory effects (Sheil et al 2004). In contrast, during E. coli infection experiment, all measured inflammatory proteins recorded a remarkable increase in LR-fed group as compared to control group.…”
Section: Discussionmentioning
confidence: 99%
“…This strain was isolated from the terminal ileum of a healthy human subject undergoing reconstructive urinary tract surgery (Dunne et al, 1999). It has been extensively studied for its probiotic properties in human trials and animal models (Dunne et al, 1999(Dunne et al, , 2001McCarthy et al, 2003;Sheil et al, 2004). Members of this species are commonly isolated from the oral and GI tracts of humans and other animals (Ahrne et al, 1998;Heilig et al, 2002;Molin et al, 1993;Rogosa et al, 1953).…”
Section: Introductionmentioning
confidence: 99%
“…salivarius strain UCC118 was isolated from the terminal ileum of a (otherwise healthy) patient undergoing urinary tract reconstructive surgery (8). This strain has been extensively studied for its probiotic properties in human trials and animal models (8)(9)(10)(11). In addition, L. salivarius UCC118 produces a two-component bacteriocin Abp118 (12), which has broad spectrum activity against Gram-positive bacteria, including methicillin-resistant Staphylococcus aureus (8).…”
mentioning
confidence: 99%